The Optimization of the Use of Informants by the Resmob Unit of the Gresik Police Criminal Investigation Unit in the Disclosure of the Crime of Battering - Antherson, Jofan Klose (Advances in Police Science Research Journal, 2024)
This article is motivated by the the cases of battering are one of the most common cases in Gresik District. An increase in the number of cases of battering occurs every year. In 2020 there were minuted 29 cases of battering, then in 2021 there were 38 cases, and in 2023 there were 63 cases. Cases of battering are also viral cases in the local community which certainly disturbs them. This caused the case of battering to become a case that received attention from the leadership of Gresik Police. The purpose of this study is to optimize the use of informants by the Resmob Unit of Gresik Police in uncovering the crime of battering. This research uses POAC management theory and SWOT analysis theory, as well as the concepts of optimization, the concept of informants, the concept of investigation, the concept of investigation, and the concept of battering. The research method used by the author is a descriptive qualitative method with data collection techniques of observation, interviews, and document studies. The data collected was then tested using triangulation techniques of sources, techniques, time, and theory. The results in the form of conclusions from this study indicate that the implementation of the use of informants by the Resmob Unit of Satreskrim Polres Gresik in revealing the crime of battering has not been optimal because the use of informants has not been maximized to reveal battering cases. This is because the number of cases of battering revealed using informants is still insufficient, there is no regulation that regulates the implementation of the use of informants in case disclosure, and there is no budget from the budget planning that supports the implementation of these activities.